STUDENTS' PROBLEM-SOLVING ABILITY IN SOLVING MATHEMATICAL PROBLEMS BASED ON POLYA'S METHOD AS A CRITERION FOR MEASURING LEARNING RESULTS - Andi Karlina (Fakultas Tarbiyah Universitas Ibrahimy, 2022)
This study aims to describe students' mathematical problem-solving ability in solving story problems. The type of research used in this study is qualitative descriptive research. This research was carried out at STKIP Paris Barantai KotaBaru. The research subjects taken were 2 students in semester V with low academic ability. The researcher chose the subject on the grounds that the student had received lecture material related to problem solving and what was found From the scores of the student's middle test and final test results, there were still students who obtained a score below 50.Data collection was carried out using written tests, interviews, and documentation. The results of the research obtained related to the subject's mathematical problem-solving ability are still very lacking, this can be seen from the 4 stages of problem-solving, namely: (1) For the stage of understanding the problem, the two research subjects in the first question seem to still have difficulty in understanding the problem; (2) For the stage of planning a settlement, both subjects apply certain strategies that are not appropriate; (3) For the stage of implementing the plan, there are still errors in the calculation operation process so it is wrong in finding answers; and (4) For the re-examination stage, S1 does not try to carry out this stage, while S2 tries to carry out the re-examination stage even though the answer results obtained are incorrect.